SAE MOTOR'S SHOWROOM'S RESPONSIBILITY TO CONSUMERS FOR PRODUCT DEFECTS IN THE USED MOTORCYCLE SALE AND PURCHASE AGREEMENT - Fiddiin, Muhammad Faqqihhu; Sulasno, Sulasno (Jurnal Locus Penelitian dan Pengabdian, 2025)
Product liability refers to the civil liability of business actors for losses experienced by consumers when using the products they provide, a concept known as product liability. Within the context of customer service management, the principle of responsibility outlined in the Consumer Protection Law is based on a presumptive principle, meaning that business actors are always presumed to be responsible. According to the principle of absolute responsibility, consumers are not required to prove the fault of business actors. Instead, consumers must demonstrate the existence of a product defect and establish the causal relationship between the defect and the injury or loss they have suffered. Under this principle, consumers still bear the burden of proving that the losses incurred are directly caused by defective products. This research employs a qualitative method using an empirical juridical approach. The primary data source is the sale and purchase agreement and the documented responsibilities of the business actor, while secondary data is drawn from books, journals, encyclopedias, dictionaries, and virtual sources. Data management techniques include interviews, direct observation, surveys, and the distribution of questionnaires. The results of this study indicate that the responsibility of the Sae motor showroom to consumers, in the context of customer service management, is evident when addressing product defects in the sales agreement for purchasing a used motorcycle.